Proceedings of the 2019 Conference on Empirical Methods in Natural Language Processing and the 9th International Joint Conferen 2019
DOI: 10.18653/v1/d19-1534
|View full text |Cite
|
Sign up to set email alerts
|

Do NLP Models Know Numbers? Probing Numeracy in Embeddings

Abstract: The ability to understand and work with numbers (numeracy) is critical for many complex reasoning tasks. Currently, most NLP models treat numbers in text in the same way as other tokens-they embed them as distributed vectors. Is this enough to capture numeracy? We begin by investigating the numerical reasoning capabilities of a state-of-the-art question answering model on the DROP dataset. We find this model excels on questions that require numerical reasoning, i.e., it already captures numeracy. To understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(176 citation statements)
references
References 17 publications
3
172
1
Order By: Relevance
“…First, that the OBESITY STATUS and OBESITY TYPES datasets contain much more numerical attributes (anthropometric information) than the SMOKING STATUS dataset. In this sense, it has been shown that BERT may not work properly representing numbers, while regular expressions allow representing complex sequential patterns, including numerical attributes [18], [22], [23]. Second, the SMOKING STATUS dataset presents temporal data and negations in the texts, and regular expressions need more examples to abstract the information.…”
Section: Discussionmentioning
confidence: 99%
“…First, that the OBESITY STATUS and OBESITY TYPES datasets contain much more numerical attributes (anthropometric information) than the SMOKING STATUS dataset. In this sense, it has been shown that BERT may not work properly representing numbers, while regular expressions allow representing complex sequential patterns, including numerical attributes [18], [22], [23]. Second, the SMOKING STATUS dataset presents temporal data and negations in the texts, and regular expressions need more examples to abstract the information.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context and drawing inspiration from [37], we propose a recursive approach that estimates the length of subsentence in an input sentence. We refer tp the length of subsentence as coverage, c, which is a scalar and computed as c = M N × κ, where M and N are the length of subsentence and input sentence, respectively.…”
Section: Coverage Model For Subsentence Extractionmentioning
confidence: 99%
“…Recently, Kaushik et Numeric reasoning Numeric reasoning in Natural Language processing has been recognized as an important part in entailment models (Sammons et al, 2010) and reading comprehension (Ran et al, 2019). Wallace et al (2019) studied the capacity of different models on understanding numerical operations and show that BERT-based model still have headroom. This motivates the use of the synthetic generation approach to improve numerical reasoning in our model.…”
Section: Counterfactual Data Generationmentioning
confidence: 99%